Influences of (in)congruences in psychological entitlement and felt obligation on ethical behavior - Chen, Qin; Shen, Yifei; Zhang, Li; Zhang, Zhenduo; Zheng, Junwei; Xiu, Jing (Frontiers in Psychology, 2023)
Psychological entitlement and felt obligation are two correlated but distinctive conceptions. Prior studies have mainly explored their influences on employees’ (un)ethical behavior respectively. Recently, several studies suggest the interactive impacts of psychological entitlement with felt obligation on individual behavioral choices. In line with and extending this line of research, this study focusses on the influences of (in)congruences in psychological entitlement and felt obligation on employees’ (un)ethical behavior. A two-wave multi-source questionnaire survey was adopted to collect 202 matched questionnaires from Chinese full-time workers. The polynomial regression with response surface analysis was employed to test the hypotheses. The results indicated that: 1) employees have higher levels of work engagement and helping behavior but lower levels of unethical behavior when their psychological entitlement and felt obligation are balanced at higher levels than lower levels; 2) employees have higher levels of work engagement and helping behavior but lower levels of unethical behavior when they have higher level of felt obligation with lower level of psychological entitlement compared to lower level of felt obligation with higher level of psychological entitlement; 3) work engagement mediates the relationship between (in)congruences in psychological entitlement and felt obligation and employee helping behavior and unethical behavior. This study provides a novel insight into the interactive influences of (in)congruence in psychological entitlement and felt obligation on employee ethical behavioral choices.